Modified Greedy Physical Link Scheduling Algorithm for Improving Wireless Mesh Network Performance - Nachwan Mufti Adriansyah; Muhamad Asvial; Bagio Budiardjo (Universitas Ahmad Dahlan, 2015)
The algorithm to allocate mesh active link to radio resource timeslot in wireless mesh network (WMN) is investigated. This paper proposes the novel method to allocate multiple links in one timeslot for improving the wireless mesh network throughput via spatial time division multiple access (STDMA) protocol. The throughput improvement is obtained by modifying greedy based algorithm that is widely known as a low complexity algorithm. We propose and investigate new parameters in the greedy based algorithm that can be used as scheduling control parameters, i.e. interference weight, scheduling weight, and the sum of link’s degree. Simulation results indicate that this approximation increases network performance in throughput and length of scheduling performance closed to the upper bound performance that is achieved by the algorithm that uses the physical interference model.